2020
DOI: 10.1155/2020/8870783
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Opposite Learning Assisted Grasshopper Optimization Algorithm for the Flexible JobScheduling Problem

Abstract: Job shop scheduling problem (JSP) is one of the most difficult optimization problems in manufacturing industry, and flexible job shop scheduling problem (FJSP) is an extension of the classical JSP, which further challenges the algorithm performance. In FJSP, a machine should be selected for each process from a given set, which introduces another decision element within the job path, making FJSP be more difficult than traditional JSP. In this paper, a variant of grasshopper optimization algorithm (GOA) named dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In this section, Fdata is used to test the performance of the proposed algorithm, and the results of the proposed DIGWO are compared with those of recent studies AIA, EPSO, MIIP and DOLGOA [31,55,67,68]. In order to eliminate randomness during the experiment, the results of 20 independent runs are shown in Table 15.…”
Section: Comparison Results In Fdatamentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, Fdata is used to test the performance of the proposed algorithm, and the results of the proposed DIGWO are compared with those of recent studies AIA, EPSO, MIIP and DOLGOA [31,55,67,68]. In order to eliminate randomness during the experiment, the results of 20 independent runs are shown in Table 15.…”
Section: Comparison Results In Fdatamentioning
confidence: 99%
“…Feng et al suggested a dynamic opposite learning assisted grasshopper optimization algorithm (DOLGOA). The dynamic opposite learning (DOL) strategy is used to improve the utilization capability of the algorithm [31]. Li et al introduced a diversified operator im-perialist competitive algorithm (DOICA), which requires minimum makespan, total delay, total work and total energy consumption [32].…”
Section: Introductionmentioning
confidence: 99%
“…The manufacturing industry plays an indispensable role in the economic development and social construction of a country [9,10]. At the same time, the manufacturing industry is also an area where a country invests a tremendous amount of energy consumption [11,12].…”
Section: Introductionmentioning
confidence: 99%